Repatriation The Pagar Mangkuk Sunan Muria to Empowering Rural Community in Muria Region - Muhammad Farid; Warto Warto; Marimin Marimin (International Journal of Science and Applied Science: Conference Series, 2022)
The teachings of Tapangeli and Pagar Mangkuk are known by some people as practice that were once taught by Raden Umar Said (Sunan Muria). It is not widely known because there are many contradictory opinion that result in the decadence value of intangible cultural heritage itself. Recently, a communal movement emerged that was initiated by the people in Kampung Budaya Piji Wetan, Lau Village, Dawe District, Kudus Regency. They made a movement to repatriation the teachings of Tapangeli and Pagar Mangkuk Sunan Muria based on perspective of performing arts. Using a qualitative approach, this study tries to narrate social praxis and the role of the cultural economy for the people of the Kampung Budaya Piji Wetan, Lau. This study also narrate their method to use culture as the main foundation for build a friendly economic ecosystem and able to support their daily needs. They also have several educational and economic programs have emerged that can be used an effort to promote village culture to support the welfare of its people. Again, this study attemps to dissect their methodology so that it can be used as a reference for other village in the Muria region with almost similar socio-cultural conditions.